The Relationship Between Midwives' Knowledge Level on Obstetric Emergency Management and Readiness to Handle Cases in the Emergency Room (PONEK) of Muara Teweh Regional Hospital - Rima Yani; Reny Retnaningsih (Lembaga Pengembangan Kinerja Dosen, 2025)
Obstetric emergencies are a major cause of maternal mortality, most of which can be prevented through prompt and appropriate treatment. Midwives, as health workers assigned to the Emergency Department (ED) of PONEK, play a strategic role in early detection and initial management of obstetric emergencies, thus their knowledge level is an important factor in determining preparedness for treatment. This study aims to analyze the relationship between midwives' knowledge level regarding obstetric emergency management and their preparedness for handling obstetric emergencies in the Emergency Department (ED) of PONEK of Muara Teweh Regional Hospital. This study used an observational analytical design with a cross-sectional approach. The study sample consisted of 28 midwives selected using a total sampling technique. Data were collected using a structured questionnaire to measure their knowledge level and preparedness for handling obstetric emergencies. Data analysis was performed descriptively and inferentially using the Fisher's Exact Test. The results showed that more than half of the midwives had a good level of knowledge and preparedness for handling obstetric emergencies. Inferential analysis showed a highly significant relationship between midwives' knowledge level and their preparedness for obstetric emergencies (p < 0.001). It was concluded that midwives' knowledge level was closely related to their preparedness for obstetric emergencies in the PONEK Emergency Department of Muara Teweh Regional Hospital. This finding underscores the importance of strengthening midwives' knowledge through ongoing training, clinical simulations, and routine supervision to improve clinical preparedness and ensure the safety of mothers and babies in emergency obstetric care.